UV PHOTOELECTRON-SPECTRA OF INDIUM(I) AND THALLIUM(I) CYCLOPENTADIENIDES - Egdell, R; Fragala, I; Orchard, A (1978)
Vapour-phase He I and He II photoelectron spectra of the cyclopentadienides of indium(I) and thallium(I) are reported. The discussion concentrates on the implications of the changes in band intensity that are observed on switching from He I to He II excitation, and on the nature of the additional structure revealed in the He II spectra. © 1978.